ANALISIS KESEDIAAN MASYARAKAT MENERIMA PROGRAM KONSOLIDASI TANAH PERKOTAAN PADA KAWASAN PERMUKIMAN KUMUH BERAT - Siregar, Muhammad Arifin; Soetjipto, Widyono (Jurnal Aspirasi, 2013)
The research aims to determine whether the people in the slum areas are willing to accept urban land consolidation program and what variables that effect. This study uses case in the RW 014 Kebon Melati, Central Jakarta. Primary data were obtained from 100 respondents, using qualitative descriptive analysis and regression analysis logit model. The results showed that the percentage of people who are willing to accept the program amounted to 64%. The variables that significantly effect the decision to accept the program are age, gender, occupation, region of origin, family size, land area, number of floors, length of stay, age of building, number of rooms, the guarantee of getting Certificate Flats and compensation relocation costs.